2019
DOI: 10.3390/cancers11081182
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Signaling in Ovarian Cancer

Abstract: The NF-κB signaling pathway is a master and commander in ovarian cancer (OC) that promotes chemoresistance, cancer stem cell maintenance, metastasis and immune evasion. Many signaling pathways are dysregulated in OC and can activate NF-κB signaling through canonical or non-canonical pathways which have both overlapping and distinct roles in tumor progression. The activation of canonical NF-κB signaling has been well established for anti-apoptotic and immunomodulatory functions in response to the tumor microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 107 publications
(176 reference statements)
3
51
0
Order By: Relevance
“…While this is the first study to demonstrate an association with clinical disease prognosis, several additional lines of mechanistic evidence support a pro-tumorigenic role for non-canonical NF-κB signaling independent of the canonical pathway [ 35 ]. We previously found that downregulation of cyclooxygenase-1 (COX-1) expression, an established pro-tumor mediator in ovarian cancer, resulted in reduced expression of multiple non-canonical NF-κB signaling components, including RELB , NFKB2 (p100/p52), CHUK (IKKα), and MAP3K14 (NF-κB-inducing kinase); in contrast, expression of canonical NF-κB pathway members was not changed by COX-1 knockdown [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this is the first study to demonstrate an association with clinical disease prognosis, several additional lines of mechanistic evidence support a pro-tumorigenic role for non-canonical NF-κB signaling independent of the canonical pathway [ 35 ]. We previously found that downregulation of cyclooxygenase-1 (COX-1) expression, an established pro-tumor mediator in ovarian cancer, resulted in reduced expression of multiple non-canonical NF-κB signaling components, including RELB , NFKB2 (p100/p52), CHUK (IKKα), and MAP3K14 (NF-κB-inducing kinase); in contrast, expression of canonical NF-κB pathway members was not changed by COX-1 knockdown [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, overexpression of p52 promotes lung tumorigenesis in mice, and associations have been demonstrated between non-canonical NF-κB signaling, p52-gene targets, and worse prognosis in human lung adenocarcinoma cases [ 33 ]. Further studies of in vitro and in vivo models of ovarian cancer have shown that non-canonical NF-κB signaling promotes cell growth and tumorigenicity as well as cancer stem cell self-renewal [ 31 , 32 , 34 , 35 ]. Aberrant expression of tissue transglutaminase in ovarian tumors has been implicated as an upstream regulator of p52 expression and non-canonical signaling, ultimately contributing to disease progression and intraperitoneal metastasis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor-Kappa B (NF-κB) is a well known transcription factor associated with almost all aspects of life activity (18). It consists of five subunits, namely c-Rel, Rel A (p65), Rel B, NF-κB1 (p105/p50), and NF-κB2 (p100/p52) (19). NF-κB plays a very important role in the progression of tumors by regulating multiple downstream targeted genes (19).…”
Section: Introductionmentioning
confidence: 99%
“…It consists of five subunits, namely c-Rel, Rel A (p65), Rel B, NF-κB1 (p105/p50), and NF-κB2 (p100/p52) (19). NF-κB plays a very important role in the progression of tumors by regulating multiple downstream targeted genes (19). A lot of studies indicated that NF-κB signaling is abnormally activated in NHL (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%